حقوق المرأة: دراسة الأديان والمجتمعات المختلفة: Woman’s Rights: A Study of different Religions and Societies (Al-Qamar, 2019)
Women's rights and their status is a hotly debated issue today. In this perspective, the present article examines the status of women in Greek, Indian and Roman civilizations and in religions such as Judaism, Christianity and Hinduism. It finds that that the status of women in the referred societies and religions has been much lower than that of Islam. Islam has ensured all the rights of women. The paper argues that it is because of Muhammad and Islam that women get rights that are not available to them even in modern times and developed nations.
Keywords: Women; status; religions; Societies